Clinical impact of first-line chemotherapy combined with immune checkpoint inhibitors for limited-stage small cell lung cancer patients: a real-world propensity score matching study - Hu, Quanman; Zhou, Chenyi; Zhao, Fei; Song, Xiaoru; Ding, Yuan; Wang, Xiyin; Wu, Boying; Wang, Huina; Chen, Shuaiyin; Jia, Bin (Frontiers in Immunology, 2026)
BackgroundFindings from the ADRIATIC clinical trial revealed that adjuvant treatment with durvalumab following chemoradiotherapy (CRT) in limited-stage small cell lung cancer (LS-SCLC) significantly improved both overall survival (OS) and progression-free survival (PFS). However, the clinical impact remains uncertain in real-world clinical practice.Materials and methodsWe gathered data of LS-SCLC patients at the First Affiliated Hospital of Zhengzhou University and conducted propensity score-matched analysis (PSM), Kaplan-Meier (K-M) method and Cox proportional hazards regression.ResultsPrior to PSM, survival results demonstrated the mOS of the chemotherapy group was 20.34 months (95% confidence interval (CI): 18.80 - 23.57 months), whereas that of the chemotherapy + ICIs group was 26.38 months (95% CI: 22.97 - 38.90 months); the hazard ratio (HR) was 0.603 (95% CI: 0.413 - 0.880, P = 0.008, sample size: 102 vs 66). Simultaneously, the mPFS of the chemotherapy + ICIs group was also greater than that of the chemotherapy group, being 10.37 months (95% CI: 9.03 - 12.90 months) and 7.87 months (6.63 - 9.73 months), HR = 0.651 (95% CI: 0.457 - 0.927). After 1:1 matching for basic variables in the chemotherapy group (sample size: 66), its mOS was at 20.22 months, and mPFS was longer at 8.50 months. The multivariate analysis presented that radiotherapy, systemic immune-inflammation index (SII) > 666.29, and platelet-to-lymphocyte ratio (PLR) > 261.39 were independent prognostic factors for OS.ConclusionThese results offer reliable references for clinicians when formulating treatment strategies for LS-SCLC patients and also provide support for future clinical trials.